2014
DOI: 10.1007/s40258-014-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Economics of Type 2 Diabetes Mellitus Prevention: A Literature Review of Methods

Abstract: Our objective was to review modelling methods for type 2 diabetes mellitus prevention cost-effectiveness studies. The review was conducted to inform the design of a policy analysis model capable of assisting resource allocation decisions across a spectrum of prevention strategies. We identified recent systematic reviews of economic evaluations in diabetes prevention and management of obesity. We extracted studies from two existing systematic reviews of economic evaluations for the prevention of diabetes. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…The model was originally developed using a new conceptual modelling framework for complex public health models, 273 in collaboration with a project stakeholder group comprising health economists, public health specialists, research collaborators from other SPHR groups, diabetologists, local commissioners and lay members. A review of existing diabetes prevention models was undertaken to inform conceptual model development, 274 resulting in the model including multiple diabetes risk factors (in particular both BMI and impaired fasting glucose) and complications of diabetes and obesity.…”
Section: Implementation Of Mapping Steps To Risk Factorsmentioning
confidence: 99%
“…The model was originally developed using a new conceptual modelling framework for complex public health models, 273 in collaboration with a project stakeholder group comprising health economists, public health specialists, research collaborators from other SPHR groups, diabetologists, local commissioners and lay members. A review of existing diabetes prevention models was undertaken to inform conceptual model development, 274 resulting in the model including multiple diabetes risk factors (in particular both BMI and impaired fasting glucose) and complications of diabetes and obesity.…”
Section: Implementation Of Mapping Steps To Risk Factorsmentioning
confidence: 99%
“…However, it is necessary to consider various risk factors for diabetes, including related complications and comorbidities. Watson et al [29] reviewed over 100 studies and concluded that, "None of the identified papers included all of these features" ( [29], p. 250). Therefore, we employed regression-type models.…”
Section: Models For the Analysis Of Losmentioning
confidence: 99%
“…However, because of differences in the model structures used, it has not been possible to compare their relative cost‐effectiveness. A recent review of economic evaluations for diabetes prevention interventions identified that to compare prevention interventions within a common framework it is necessary to incorporate multiple risk factors for diabetes, diabetes‐related complications and obesity‐related comorbidity outcomes .…”
Section: Introductionmentioning
confidence: 99%